Durkheim in dialogue : a centenary celebration of the elementary forms of religious life - Hausner, Sondra L. (Methodology and history in anthropology., 2013)
One hundred years after the publication of the great sociological treatise, The Elementary Forms of Religious Life, this new volume shows how aptly Durkheim's theories still resonate with the study of contemporary and historical religious societies. The volume applies the Durkheimian model to multiple cases, probing its resilience, wondering where it might be tweaked, and asking which aspects have best stood the test of time. A dialogue between theory and ethnography, this book shows how Durkheimian sociology has become a mainstay of social thought and theory, pointing to multiple.